Neurotransmitters and Neuropeptides: New Players in the Control of Islet of Langerhans' Cell Mass and Function. Issue 4 (10th September 2015) - Di Cairano, Eliana S.; Moretti, Stefania; Marciani, Paola; Sacchi, Vellea Franca; Castagna, Michela; Davalli, Alberto; Folli, Franco; Perego, Carla
Abstract : Islets of Langerhans control whole body glucose homeostasis, as they respond, releasing hormones, to changes in nutrient concentrations in the blood stream. The regulation of hormone secretion has been the focus of attention for a long time because it is related to many metabolic disorders, including diabetes mellitus. Endocrine cells of the islet use a sophisticate system of endocrine, paracrine and autocrine signals to synchronize their activities. These signals provide a fast and accurate control not only for hormone release but also for cell differentiation and survival, key aspects in islet physiology and pathology. Among the different categories of paracrine/autocrine signals, this review highlights the role of neurotransmitters and neuropeptides. In a manner similar to neurons, endocrine cells synthesize, accumulate, release neurotransmitters in the islet milieu, and possess receptors able to decode these signals. In this review, we provide a comprehensive description of neurotransmitter/neuropetide signaling pathways present within the islet. Then, we focus on evidence supporting the concept that neurotransmitters/neuropeptides and their receptors are interesting new targets to preserve β‐cell function and mass. A greater understanding of how this network of signals works in physiological and pathological conditions would advance our knowledge of islet biology and physiology and uncover potentially new areas of pharmacological intervention. J. Cell. Physiol. 231: 756–767, 2016. © 2015 Wiley Periodicals, Inc.